2003
DOI: 10.1128/jb.185.13.3804-3812.2003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of the Copper-Transporting Efflux System CusCFBA of Escherichia coli

Abstract: In contrast to other well-studied CBA-type heavy metal efflux systems, Cus was shown to be a tetrapartite resistance system that involves the novel periplasmic copper-binding protein CusF. These data provide additional evidence for the hypothesis that Cu(I) is directly transported from the periplasm across the outer membrane by the Cus complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
522
1
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(551 citation statements)
references
References 66 publications
(87 reference statements)
19
522
1
4
Order By: Relevance
“…86 Interestingly, ibeB (a gene synonymous with cusC) in C. sakazakii has been reported, belonging to constellate of genes encoding a copper and silver resistance cation efflux system, ultimately allowing the invasion to brain microvascular endothelial cells (BMEC) cells. 23, 87 When assessed by Kucerova et al 23 it was discovered that the entire cation efflux operon (cusA, cusB and cusC) and its regulatory gene cusR were present in isolates colligated with neonatal infections (including C. sakazakii ATCC 29544 T , 696, 701, 767, C. malonaticus and C. turicensis) and absent in the other strains evaluated (C. sakazakii B894, ATCC 12868, 20, C. dublinensis and C. muytjensii).…”
Section: Efflux Systemmentioning
confidence: 99%
“…86 Interestingly, ibeB (a gene synonymous with cusC) in C. sakazakii has been reported, belonging to constellate of genes encoding a copper and silver resistance cation efflux system, ultimately allowing the invasion to brain microvascular endothelial cells (BMEC) cells. 23, 87 When assessed by Kucerova et al 23 it was discovered that the entire cation efflux operon (cusA, cusB and cusC) and its regulatory gene cusR were present in isolates colligated with neonatal infections (including C. sakazakii ATCC 29544 T , 696, 701, 767, C. malonaticus and C. turicensis) and absent in the other strains evaluated (C. sakazakii B894, ATCC 12868, 20, C. dublinensis and C. muytjensii).…”
Section: Efflux Systemmentioning
confidence: 99%
“…The CusR/CusS system is predicted to monitor the periplasmic concentration of the metal ion, to modulate the expression of an RND-type copper efflux pump, encoded by the cusCFBA operon (Franke et al, 2003;Munson et al, 2000). Recently, it was shown that transcription of a second, uncharacterized, two-component system, encoded by the yedWV operon, is activated by copper ions in a CusR-dependent manner (Yamamoto & Ishihama, 2005), although its role in copper tolerance remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular or periplasmic copper trafficking domains, however, function in environments that are more oxidizing than the cytosol and frequently have less well understood methionine-rich sequences 3-8 . The cus operon encodes a bacterial copper homeostasis system with several methionine-motif proteins 5,9,10 , including the periplasmic protein CusF, which is thought to serve as copper chaperone or regulator 5,6 . CusF binds Cu(I) in vitro 11 , and a methionine-rich Cu(I) site was proposed 6 based on an apo-CusF structure and NMR chemical shift data.…”
mentioning
confidence: 99%